The Challenge of Identity Politics in The 2024 Election - Imam Fadli; Mugito Mugito; Noman Kresna Martha Sena; Nikmatus Syarofah; Eva Nur Laily Rohmah; AHMAD SHOLIKIN (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Identity and representation are two significant things in human life. While religion and ethnicity are two things that become the identity and representation of humans. The democratic process in Indonesia is inseparable from the political orientation of identity and representation. This research is qualitative in nature, focusing on the case of the 2018-2022 DKI Regional Election in the second round. The case will be analyzed using the theory of identity politics and political representation. The results show that identity politics orientation and political representation affect the democratic process. Democratization that upholds freedom is the basis for every individual to actualize themselves, including in political matters. The individual freedom guaranteed by the constitution in Indonesia reflects the high popularity of this democratic system. However, this freedom has ultimately made the divide between identities (religion, ethnicity, language, gender, etc.) in Indonesia clearer, especially in relation to the nation's political issues. The issue of religion and nationalism are two identities that are currently being debated in Indonesia. The polemics of identity politics are increasingly tapering until the emergence of truth claims that one interest group is better than other interest groups, this interest affair then begins to divide the nation that previously upheld differences.